Effect of Hot Water Treatment on the Chemical, Sensorial Properties and Ripening Quality of Chaunsa Mango (Mangifera indica L.) - Muhammad Shahnawaz,; Saghir Ahmed Sheikh,; Aasia Akbar Panwar,; Shahzor Gul Khaskheli ,; Fahad Ahmed Awan, (Journal of Basic & Applied Sciences, 2012)
The study was carried out to investigate the effects of hot water treatment on the chemical, sensorial properties and ripening quality of Chaunsa mango during the year 2010-11. Results showed that mangoes treated with hot water of 55oC and stored at room temperature (38+ 4oC) were ripened in 3 days, whereas mangoes treated with hot water treatment of 45oC ripened in 4 days, without hot water treatment were ripened in 5 days. Chemical properties like total acidity, vitamin C content, TSS, total sugars, reducing sugar, non reducing sugar were determined in mangoes treated with hot water at 55oC for 20 minutes and stored at room temperature, followed by hot water treatment of 45oC at 30 minutes. Early ripening of mangoes and best sensorial properties were also observed as peel color, fruit softness, pulp color, taste/flavor, texture and aroma. The study revealed that mangoes treated in hot water were ripened in better quality than control. Furthermore, the sensorial properties of the treated mangoes were scored higher and quality wise better than control.